The globalization of regional clusters: between localization and internationalization - Fornahl, Dirk; Grashof, Nils (New horizons in regional science series, 2021)
Contents: Introduction: Regional clusters and internationalization - complementary or contrasting fields of research? / Nils Grashof, Dirk Fornahl and Julius Becker -- Part I: Rethinking clusters: Conceptualization of cluster internationalization: 1. Strategic cluster coupling / Robert Hassink -- 2. From the machine learning region to the deep learning region: Tesla, darktrace and deepmind as internationalized local to global cluster firms / Philip Cooke -- 3. Embedding cluster transformation in global sectoral resilience dynamics: Conceptual considerations and the example of automotive production / Martina Fromhold-Eisebith -- Part II: The processes of cluster internationalization and their implications -- 4. Migrants and cluster internationalization: Case studies of antwerp and tel aviv / Sebastian Henn and Susann Schäfer -- 5. Regional clusters in transition economies: Solving institutional voids to generate internationalization advantages / Tine Lehmann and Nobina Roy -- Part III: Cluster internationalization and firm performance: 6. Macroeconomic impacts on firm performance and place-based cluster policies in the Netherlands / Jeroen van Haaren, Frank van Oort and Jan-Daan Maasland -- 7. Knowledge bases, innovation and multi-scalar relationships: Which kind of territorial boundedness of industrial clusters? / Franz Tödtling and Alexander Auer -- 8. Radical innovations in clusters: The role of cluster internal and external relationships / Nils Grashof and Thomas Brenner -- Index.